Local coupling of cerebral blood flow to cerebral glucose metabolism during inhalational anesthesia in rats: Desflurane versus Isoflurane - Lenz, Christian; Frietsch, Thomas; Fütterer, Carsten Dietmar; Rebel, Annette; Ackern, Klaus van; Kuschinsky, Wolfgang; Waschke, Klaus F. (Anesthesiology, 1999)
It is not known whether the effects of desflurane on local cerebral glucose utilization (LCGU) and local cerebral blood flow (LCBF) are different from those of other volatile anesthetics.Using the autoradiographic iodoantipyrine and deoxyglucose methods, LCGU, LCBF, and their overall means were measured in 60 Sprague-Dawley rats (10 groups, n = 6 each) during desflurane and isoflurane anesthesia and in conscious controls.During anesthesia, mean cerebral glucose utilization was decreased compared with conscious controls: 1 minimum alveolar concentration (MAC) desflurane: -52%; 1 MAC isoflurane: -44%; 2 MAC desflurane: -62%; and 2 MAC isoflurane: -60%. Local analysis showed a reduction of LCGU in the majority of the 40 brain regions analyzed. Mean cerebral blood flow was increased: 1 MAC desflurane: +40%; 1 MAC isoflurane: +43%; 2 MAC desflurane and 2 MAC isoflurane: +70%. LCBF was increased in all brain structures investigated except in the auditory cortex. No significant differences (P < 0.05) could be observed between both anesthetics for mean values of cerebral glucose use and blood flow. Correlation coefficients obtained for the relation between LCGU and LCBF were as follows: controls: 0.95; 1 MAC desflurane: 0.89; 2 MAC desflurane: 0.60; 1 MAC isoflurane: 0.87; and 2 MAC isoflurane: 0.68.Differences in the physicochemical properties of desflurane compared with isoflurane are not associated with major differences in the effects of both volatile anesthetics on cerebral glucose utilization, blood flow, and the coupling between LCBF and LCGU.